Medicaid and Teen Suicide - Dave E. Marcotte; Alexandra Rakus (Institute of Labor Economics (IZA), 2024)
We examine whether increases in Medicaid coverage among teens reduced suicide risk. Youth are at elevated risk for depression but receive the least care. We exploit state-level variation in Medicaid coverage controlling for crowd-out to identify effects on risk for suicide. We build an age-group/state/year panel measuring suicide rates from CDC data and age-specific rates of insurance coverage from the American Community Survey. We estimate that among those between the ages of 15 and 19, suicide rates fell by 0.023 log points, or 1 percent of the mean with each 1 percent increase in the population of teens covered by Medicaid. This decline was larger for teens than any other group. We assess whether our TWFE estimated effect of a continuous treatment approximates an average causal response by comparing treatment effects at different margins. We form 47 treatment-control groupings of states changing key features of Medicaid enrollment policies in different years along with always/never treated states. Our treatment effects at these various margins are within confidence bounds for our average effects. We provide the first evidence on the role of public health insurance coverage on teen suicide in the U.S.
Keywords: 330